Persuasion, beyond the Earthly - Delgado Mora, Jairo Omar; Pamplona Camargo, Luz Mireya (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2019)
Permanently we try to persuade someone: sell a product, get a job, get a discount. In this way, the document aims to determine what those qualities of a person capable of persuading are. Initially and as a first added value, the subject has been considered even from the divine perspective, an instrument of confrontation with other authors with the aim of enriching the theme. As a second added value, in the end a practical exercise is done through which the found qualities become evident.